Global warming and African climate change: a reassessment - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark (2005)
Understanding and predicting temporal variations in African climate has become the major challenge facing African and African-specialist climate scientists in recent years. Whilst seasonal climate forecasts have taken great strides forward, we remain unsure of the ultimate causes of the lower frequency decadal and multi-decadal rainfall variability that affects some African climate regimes, especially in the Sahel region. This work examining the variability of African climate, especially rainfall, is set in the wider context of our emerging understanding of human influences on the larger, global-scale climate. Africa will be no exception to experiencing these human-induced changes in climate, although much work remains to be done in trying to isolate those aspects of African climate variability that are ‘natural’ from those that are related to human influences. African climate scientists face a further challenge in that it is in this continent that the role of land-cover changes in modifying regional climates is perhaps most marked. It is for these reasons – large internal climate variability and the confounding role of land-cover change – that climate change ‘predictions’ (or scenarios) for Africa based on greenhouse gas warming remain at a low level of confidence. Nevertheless, it is of considerable interest to try and scope the magnitude of the problem that the enhanced greenhouse effect may pose for African climate and for African resource managers.
Keywords: openalex:import

African climate change: 1900-2100 - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark; Lister, David (Climate research, 2001)
This paper reviews observed and possible future (2000-2100) continentwide changes in temperature and rainfall for Africa.For the historic period we draw upon a new observed global climate data set which allows us to explore aspects of regional climate change related to diurnal temperature range and rainfall variability.The latter includes an investigation of regions where seasonal rainfall is sensitive to El Niño climate variability.This review of past climate change provides the context for our scenarios of future greenhouse gas-induced climate change in Africa.These scenarios draw upon the draft emissions scenarios prepared for the Intergovernmental Panel on Climate Change's Third Assessment Report, a suite of recent global climate model experiments, and a simple climate model to link these 2 sets of analyses.We present a range of 4 climate futures for Africa, focusing on changes in both continental and regional seasonal-mean temperature and rainfall.Estimates of associated changes in global CO 2 concentration and global-mean sea-level change are also supplied.These scenarios draw upon some of the most recent climate modelling work.We also identify some fundamental limitations to knowledge with regard to future African climate.These include the often poor representation of El Niño climate variability in global climate models, and the absence in these models of any representation of regional changes in land cover and dust and biomass aerosol loadings.These omitted processes may well have important consequences for future African climates, especially at regional scales.We conclude by discussing the value of the sort of climate change scenarios presented here and how best they should be used in national and regional vulnerability and adaptation assessments.
Keywords: openalex:import

African climate change: 1900-2100 - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark; Lister, David (Climate research, 2001)
This paper reviews observed and possible future (2000-2100) continentwide changes in temperature and rainfall for Africa.For the historic period we draw upon a new observed global climate data set which allows us to explore aspects of regional climate change related to diurnal temperature range and rainfall variability.The latter includes an investigation of regions where seasonal rainfall is sensitive to El Niño climate variability.This review of past climate change provides the context for our scenarios of future greenhouse gas-induced climate change in Africa.These scenarios draw upon the draft emissions scenarios prepared for the Intergovernmental Panel on Climate Change's Third Assessment Report, a suite of recent global climate model experiments, and a simple climate model to link these 2 sets of analyses.We present a range of 4 climate futures for Africa, focusing on changes in both continental and regional seasonal-mean temperature and rainfall.Estimates of associated changes in global CO 2 concentration and global-mean sea-level change are also supplied.These scenarios draw upon some of the most recent climate modelling work.We also identify some fundamental limitations to knowledge with regard to future African climate.These include the often poor representation of El Niño climate variability in global climate models, and the absence in these models of any representation of regional changes in land cover and dust and biomass aerosol loadings.These omitted processes may well have important consequences for future African climates, especially at regional scales.We conclude by discussing the value of the sort of climate change scenarios presented here and how best they should be used in national and regional vulnerability and adaptation assessments.
Keywords: openalex:import

African climate change: 1900-2100 - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark; Lister, David (Climate research, 2001)
This paper reviews observed and possible future (2000-2100) continentwide changes in temperature and rainfall for Africa.For the historic period we draw upon a new observed global climate data set which allows us to explore aspects of regional climate change related to diurnal temperature range and rainfall variability.The latter includes an investigation of regions where seasonal rainfall is sensitive to El Niño climate variability.This review of past climate change provides the context for our scenarios of future greenhouse gas-induced climate change in Africa.These scenarios draw upon the draft emissions scenarios prepared for the Intergovernmental Panel on Climate Change's Third Assessment Report, a suite of recent global climate model experiments, and a simple climate model to link these 2 sets of analyses.We present a range of 4 climate futures for Africa, focusing on changes in both continental and regional seasonal-mean temperature and rainfall.Estimates of associated changes in global CO 2 concentration and global-mean sea-level change are also supplied.These scenarios draw upon some of the most recent climate modelling work.We also identify some fundamental limitations to knowledge with regard to future African climate.These include the often poor representation of El Niño climate variability in global climate models, and the absence in these models of any representation of regional changes in land cover and dust and biomass aerosol loadings.These omitted processes may well have important consequences for future African climates, especially at regional scales.We conclude by discussing the value of the sort of climate change scenarios presented here and how best they should be used in national and regional vulnerability and adaptation assessments.
Keywords: openalex:import

African climate change: 1900-2100 - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark; Lister, David (Climate research, 2001)
This paper reviews observed and possible future (2000-2100) continentwide changes in temperature and rainfall for Africa.For the historic period we draw upon a new observed global climate data set which allows us to explore aspects of regional climate change related to diurnal temperature range and rainfall variability.The latter includes an investigation of regions where seasonal rainfall is sensitive to El Niño climate variability.This review of past climate change provides the context for our scenarios of future greenhouse gas-induced climate change in Africa.These scenarios draw upon the draft emissions scenarios prepared for the Intergovernmental Panel on Climate Change's Third Assessment Report, a suite of recent global climate model experiments, and a simple climate model to link these 2 sets of analyses.We present a range of 4 climate futures for Africa, focusing on changes in both continental and regional seasonal-mean temperature and rainfall.Estimates of associated changes in global CO 2 concentration and global-mean sea-level change are also supplied.These scenarios draw upon some of the most recent climate modelling work.We also identify some fundamental limitations to knowledge with regard to future African climate.These include the often poor representation of El Niño climate variability in global climate models, and the absence in these models of any representation of regional changes in land cover and dust and biomass aerosol loadings.These omitted processes may well have important consequences for future African climates, especially at regional scales.We conclude by discussing the value of the sort of climate change scenarios presented here and how best they should be used in national and regional vulnerability and adaptation assessments.
Keywords: openalex:import; openalex:yes

African climate change: 1900-2100 - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark; Lister, David (Climate research, 2001)
This paper reviews observed and possible future (2000-2100) continentwide changes in temperature and rainfall for Africa.For the historic period we draw upon a new observed global climate data set which allows us to explore aspects of regional climate change related to diurnal temperature range and rainfall variability.The latter includes an investigation of regions where seasonal rainfall is sensitive to El Niño climate variability.This review of past climate change provides the context for our scenarios of future greenhouse gas-induced climate change in Africa.These scenarios draw upon the draft emissions scenarios prepared for the Intergovernmental Panel on Climate Change's Third Assessment Report, a suite of recent global climate model experiments, and a simple climate model to link these 2 sets of analyses.We present a range of 4 climate futures for Africa, focusing on changes in both continental and regional seasonal-mean temperature and rainfall.Estimates of associated changes in global CO 2 concentration and global-mean sea-level change are also supplied.These scenarios draw upon some of the most recent climate modelling work.We also identify some fundamental limitations to knowledge with regard to future African climate.These include the often poor representation of El Niño climate variability in global climate models, and the absence in these models of any representation of regional changes in land cover and dust and biomass aerosol loadings.These omitted processes may well have important consequences for future African climates, especially at regional scales.We conclude by discussing the value of the sort of climate change scenarios presented here and how best they should be used in national and regional vulnerability and adaptation assessments.
Keywords: openalex:import; openalex:yes

African climate change: 1900-2100 - Hulme, Mike; Doherty, Ruth M.; Ngara, Todd; New, Mark; Lister, David (Climate research, 2001)
This paper reviews observed and possible future (2000-2100) continentwide changes in temperature and rainfall for Africa.For the historic period we draw upon a new observed global climate data set which allows us to explore aspects of regional climate change related to diurnal temperature range and rainfall variability.The latter includes an investigation of regions where seasonal rainfall is sensitive to El Niño climate variability.This review of past climate change provides the context for our scenarios of future greenhouse gas-induced climate change in Africa.These scenarios draw upon the draft emissions scenarios prepared for the Intergovernmental Panel on Climate Change's Third Assessment Report, a suite of recent global climate model experiments, and a simple climate model to link these 2 sets of analyses.We present a range of 4 climate futures for Africa, focusing on changes in both continental and regional seasonal-mean temperature and rainfall.Estimates of associated changes in global CO 2 concentration and global-mean sea-level change are also supplied.These scenarios draw upon some of the most recent climate modelling work.We also identify some fundamental limitations to knowledge with regard to future African climate.These include the often poor representation of El Niño climate variability in global climate models, and the absence in these models of any representation of regional changes in land cover and dust and biomass aerosol loadings.These omitted processes may well have important consequences for future African climates, especially at regional scales.We conclude by discussing the value of the sort of climate change scenarios presented here and how best they should be used in national and regional vulnerability and adaptation assessments.
Keywords: openalex:import

The impacts of climate change on Africa - Hulme, Mike; Conway, Declan; Kelly, P. M.; Subak, Susan; Downing, TE (2007)
Many scientists, economists, and policymakers agree that the world is facing a threat from climate warming (IPCC, 2001a). The degree of the impact and its distribution is still debated. The current evidence suggests that countries in temperate and polar locations may benefit from small economic advantages because additional warming will benefit their agricultural sectors (Mendelsohn et al., 2000; Mendelsohn and Williams, 2004). Many countries in tropical and subtropical regions are expected to be more vulnerable because additional warming will affect their marginal water balance and harm their agricultural sectors (IPCC, 2001b; Tol, 2002; Mendelsohn and Williams, 2004). However, little empirical research has been done on tropical countries, so that little is known about the extent of these damages. The problem is expected to be most severe in Africa, and especially sub-Saharan Africa, where the people are poor, temperatures are high, precipitation is low, technological change has been slow, and agriculture dominates domestic economies. African farmers have adapted to their current climates, but climate change may well force large regions of marginal agriculture out of production in Africa.
Keywords: openalex:import